An annotated checklist of bryophytes of Europe, Macaronesia and Cyprus. (2nd January 2020) - Hodgetts, N. G.; Söderström, L.; Blockeel, T. L.; Caspari, S.; Ignatov, M. S.; Konstantinova, N. A.; Lockhart, N.; Papp, B.; Schröck, C.; Sim-Sim, M.; Bell, D.; Bell, N. E.; et al.
ABSTRACT: Introduction. Following on from work on the European bryophyte Red List, the taxonomically and nomenclaturally updated spreadsheets used for that project have been expanded into a new checklist for the bryophytes of Europe. Methods. A steering group of ten European bryologists was convened, and over the course of a year, the spreadsheets were compared with previous European checklists, and all changes noted. Recent literature was searched extensively. A taxonomic system was agreed, and the advice and expertise of many European bryologists sought. Key results. A new European checklist of bryophytes, comprising hornworts, liverworts and mosses, is presented. Fifteen new combinations are proposed. Conclusions. This checklist provides a snapshot of the current European bryophyte flora in 2019. It will already be out-of-date on publication, and further research, particularly molecular work, can be expected to result in many more changes over the next few years.